2023
DOI: 10.1002/acr.24960
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the EULAR/American College of Rheumatology Classification Criteria for Systemic Lupus Erythematosus in a Population‐Based Registry

Abstract: Objective Using the Manhattan Lupus Surveillance Program, a multiracial/ethnic population‐based registry, we aimed to compare 3 commonly used classification criteria for systemic lupus erythematosus (SLE) to identify unique cases and determine the incidence and prevalence of SLE using the EULAR/American College of Rheumatology (ACR) criteria. Methods SLE cases were defined as fulfilling the 1997 ACR, the Systemic Lupus International Collaborating Clinics (SLICC), or the EULAR/ACR classification criteria. We qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…In clinical practice, it is sometimes difficult to differentiate SLE and Sjögren's disease due to common clinical and serological features. 28 Assan et al 29 reported that 2019 EULAR/ACR criteria were met in only 4.2% of Sjögren's disease patients and they claimed that 2019 EULAR/ACR criteria were able to discriminate these two diseases in clinical practice, which was not entirely supported by our observations.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In clinical practice, it is sometimes difficult to differentiate SLE and Sjögren's disease due to common clinical and serological features. 28 Assan et al 29 reported that 2019 EULAR/ACR criteria were met in only 4.2% of Sjögren's disease patients and they claimed that 2019 EULAR/ACR criteria were able to discriminate these two diseases in clinical practice, which was not entirely supported by our observations.…”
Section: Discussioncontrasting
confidence: 72%
“…35 patients (2.3%) fulfilled only 1997 ACR criteria. 28 When we analyzed the twelve patients that failed to meet both recent criteria, we found that two of these patients could be classified as SLE by 1997 ACR criteria. The remaining 10 patients did not meet any of the three criteria.…”
Section: Discussionmentioning
confidence: 99%
“…SLE was defined as meeting at least one of the following: 1) 1997 American College of Rheumatology (ACR) ( 44 ), Systemic Lupus Erythematosus Collaborating Clinics (SLICC) ( 45 ), or 2019 European League Against Rheumatism (EULAR)/ACR classification criteria ( 46 ) as we previously described ( 47 ). Concomitant rheumatic diseases were defined using modified criteria based on available data collected in the MLSP: SjD (anti-SSA/Ro positive and evidence of keratoconjunctivitis sicca and/or xerostomia, which was our restrictive definition in the primary SjD analysis) ( 40 ), and APLS (antiphospholipid antibody positive and evidence of an arterial or venous clot).…”
Section: Methodsmentioning
confidence: 99%